Impact Of Biodiesel Demand On The Malaysian Palm Oil Industry: A Simultaneous Equations Approach - Applanaidu, SDAP; Arshad, FM; Yusop, Z; Shamsudin, MN; Alias, MH (Univ Utara Malaysia Press, 2024)
Indexed by WOS